2005
DOI: 10.1002/bem.20099
|View full text |Cite
|
Sign up to set email alerts
|

Apartment electrical wiring: A cause of extremely low frequency magnetic field exposure in residential areas

Abstract: Extremely low frequency (ELF) magnetic fields (MFs) were measured at 696 points in a room of a Japanese apartment building. The building had 124 rooms with layouts and wiring identical to those of the studied room. ELF-MFs exceeded 0.4 microT in 24% of the living space, and the maximum value, 1.8 microT, was detected at floor level. Analysis of the MF distribution revealed that 60 Hz 100 V electrical wiring for room lights within the floor and ceiling had been laid out in large rectangles, equivalent to 1 turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The low capability of predicting 72-h ELF magnetic filed by the regression model was likely owing to lack of consideration of some other vital sources of indoor ELF magnetic field. Many studies have empirically demonstrated that a number of factors including loads on external power lines , electrical wiring in residential areas (Moriyama and Yoshitomi, 2005), residence age (Kavet et al, 1999), ground current and service loops (Kavet et al, 1999), and the use of domestic appliances (Mezei et al, 2001) are associated indoor ELF magnetic filed. Although previous studies demonstrated that high voltage transmission lines alone may contribute dominantly and substantially to the residential ELF magnetic filed (Levallois et al, 1995;The´riault and Li, 1997) at home close to the line, and that measured ELF magnetic field correlated well with the calculated field for residences within 50 m away from hightension power lines (The´riault and , the findings from this study indicated that consideration of high-tension power lines alone might be far from sufficient to predict residential exposure to 72-h ELF magnetic fields even in households very close to high-tension power lines.…”
Section: Discussionmentioning
confidence: 99%
“…The low capability of predicting 72-h ELF magnetic filed by the regression model was likely owing to lack of consideration of some other vital sources of indoor ELF magnetic field. Many studies have empirically demonstrated that a number of factors including loads on external power lines , electrical wiring in residential areas (Moriyama and Yoshitomi, 2005), residence age (Kavet et al, 1999), ground current and service loops (Kavet et al, 1999), and the use of domestic appliances (Mezei et al, 2001) are associated indoor ELF magnetic filed. Although previous studies demonstrated that high voltage transmission lines alone may contribute dominantly and substantially to the residential ELF magnetic filed (Levallois et al, 1995;The´riault and Li, 1997) at home close to the line, and that measured ELF magnetic field correlated well with the calculated field for residences within 50 m away from hightension power lines (The´riault and , the findings from this study indicated that consideration of high-tension power lines alone might be far from sufficient to predict residential exposure to 72-h ELF magnetic fields even in households very close to high-tension power lines.…”
Section: Discussionmentioning
confidence: 99%
“…Extremely low frequency (ELF) electromagnetic fields (EMFs) are produced when electricity is generated and transmitted, such as in transmission lines, railways, and electrical home appliances [ 1 ]. EMFs of 0–300 Hz are defined as ELF-EMFs.…”
Section: Introductionmentioning
confidence: 99%
“…EMFs of 0–300 Hz are defined as ELF-EMFs. We are exposed daily to 50–60 Hz ELF-EMFs produced by most electrical home appliances [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…and electrical wiring within walls [Moriyama and Yoshitomi, 2005], as well as portable sources including office equipment, power cables, computer, printers, air conditioners and fans [Mezei et al, 2001]. It is also noticeable that the standard deviations were higher in the exposed group (0.51 mT) compared to those of the non-exposed group (0.27 mT), which may be related to the hourly fluctuations in electricity loading of the power lines, as well as the rapid reduction in the magnetic field which is discernible with increasing distance from the high-voltage power lines.…”
Section: Discussionmentioning
confidence: 99%